The search for extraterrestrial life : essays on science and technology - Day, P. (Proceedings of the Royal Institution., 1998)
This volume of selected Evening Discourses from the Royal Institution offers an authoritative and accessible summary of current thinking in many areas of science and technology. The subjects are wide-ranging, from studies of Venus and what they tell us about the Earth, the history and possible future of television, to the interface between art and science - using spectroscopy to analyse the pigments in Medieval manuscripts. Will we be able to build machines with molecular-basedmemories? How do you deal with an historic tower `founded on jelly and slowly inclining to the point at which it is ab.